SURVEILANS KEJADIAN STUNTING PADA KEGIATAN POSYANDU DI DESA - Ahmad Ghiffari; Budi Utama; Khoirotun Niswa; Siti Nurjannah; Widiya Yolanda; Yolanda Olivia; Yurni Fadhillah (Batara Wisnu : Indonesian Journal of Community Services, 2023)
According to Bappenas, stunting in Ogan Komering Ilir Regency is one of the priority locations for interventions to reduce stunting. Students can play an active role in preventing stunting by providing education and information to the public. This activity aims to reduce the incidence of stunting by identifying stunted children. The technique used is that students collaborate with Village Midwife partners to examine children who come regularly to the Posyandu in Lubuk Makmur village in Lempuing Jaya District. Measurement of children's weight and height found that one child was stunted, and four others were at high risk of losing weight and very low height. Posyandu is likely to work together to increase public awareness of malnutrition in children by carrying out regular health checks and providing education so that the incidence of stunting can be reduced in the future